Innovation in concentrating solar power technologies: A study drawing on patent data - Frauke G. Braun; Elizabeth Hooper; Robert Wand; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Better understanding the innovative process of renewable energy technologies is important for tackling climate change. Though concentrating solar power is receiving growing interest, innovation studies so far have explored innovative activity in solar technologies in general, ignoring the major differences between solar photovoltaic and solar thermal technologies. This study relies on patent data to examine international innovative activity in concentrating solar power technologies. Our unique contribution, based on engineering expertise and detailed datawork, is a classification system matching solar thermal technologies to the International Patent Classification (IPC) system. To this end we suggest a narrowly defined set of IPC classes and a broader one of technologies relevant to CSP, but not exclusively so. We moreover exploit information from three international patent offices, the European, the United States and the Japanese patent office. Innovative activity in narrowly defined CSP technologies has experienced an early boom before 1980 and only recently showed some signs of more activity - a pattern closely resembling the R&D support path. R&D and innovation are concentrated in few high-tech countries - such as the U.S. or Germany. Large CSP potential is not a sufficient condition for innovation, only developed countries such as Australia with both CSP potential and adequate economic and scientific capabilities are found to be among the group of relevant innovators.
Keywords: O31; Q42; Q54; Q55; 330; Innovation; patent data; solar technologies; climate change; Sonnenenergie; Solaranlage; Innovation; Patent; Energieforschung; Regionale Konzentration; Hochtechnologiesektor; USA; Deutschland; Japan; EU-Staaten